Integration of Dental Implants in Conjunction with EDTA-Conditioned Dentin Grafts: An Experimental Study - Payam Farzad; Ted Lundgren; Adel Al-Asfour; Lars Andersson; Christer Dahlin (MDPI AG, 2021)
This study was undertaken to investigate the integration of titanium micro-implants installed in conjunction with previously dentin-grafted areas and to study the morphological appearance, mineral content, and healing pattern of xenogenic EDTA-conditioned dentin blocks and granules grafted to cavities in the tibial bone of rabbits. Demineralized and non-demineralized dentin blocks and granules from human premolars were implanted into cavities prepared on the lateral aspects of the tibias of rabbits. After a healing period of six months, micro-implants were installed at each surgical site. Histological examinations were carried out after 24 weeks. Characterization of the EDTA-conditioned dentin blocks was performed by means of light microscopy, dental X-rays, scanning electron microscopy, and energy dispersive X-ray analysis (EDX). No implants were found to be integrated in direct contact with the dentin particles or blocks. On the EDTA-conditioned dentin surface, the organic marker elements C and N dominated, as revealed by EDX. The hydroxyapatite constituents Ca and P were almost absent on the dentin surface. No statistically significant difference was observed between the EDTA-conditioned and non-demineralized dentin, as revealed by BIC and BA. The bone-inductive capacity of the dentin material seemed limited, although demineralization by means of EDTA indicated higher BIC and BA values in conjunction with the installed implants in the area. A 12 h EDTA treatment did not fully decalcify the grafts, as revealed by X-ray analysis.